Editorial Vol.17(1) - Sampatha Goonewardena (Journal of the College of Community Physicians, 2012)
DOI: http://dx.doi.org/10.4038/jccpsl.v17i1.4928 Journal of the College of Community Physicians of Sri Lanka Vol.17(2) June 2012